Inhibitors in AKTion: ATP-competitive vs allosteric. (26th May 2020) - Lazaro, Glorianne; Kostaras, Eleftherios; Vivanco, Igor
Abstract : Aberrant activation of the PI3K pathway is one of the commonest oncogenic events in human cancer. AKT is a key mediator of PI3K oncogenic function, and thus has been intensely pursued as a therapeutic target. Multiple AKT inhibitors, broadly classified as either ATP-competitive or allosteric, are currently in various stages of clinical development. Herein, we review the evidence for AKT dependence in human tumours and focus on its therapeutic targeting by the two drug classes. We highlight the future prospects for the development and implementation of more effective context-specific AKT inhibitors aided by our increasing knowledge of both its regulation and some previously unrecognised non-canonical functions.